2021
DOI: 10.1246/cl.210435
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of the Huynh Electronic Parameter (HEP)

Abstract: The Huynh electronic parameter (HEP) is a modern alternative method to determine ligand donor strengths by 13C NMR spectroscopy of metal NHC complexes containing the ligand of interest. Using the HEP, the electronic properties of numerous classical Werner-type and organometallic ligands have been evaluated thus far. Moreover, it has been extended to the HEP2, which provides a means to measure bidentate chelators. This Highlight Review covers recent applications of the HEP and its variants from 2016 onwards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Complexes 3a–d and 4a–d all contain the i Pr 2 -bimy carbene ligand making them suitable probes to measure the electron-donating strengths of the transoid L and L 2 ligands using Huynh's electronic parameters (HEP & HEP2). 11 The detailed results and discussions are given in the ESI †. Here, a summary of the HEP2 scale was drawn to showcase that the current C NHC ^C sp3 chelators are stronger donors than the charge-neutral N^N (158.2–163.4 ppm), C NHC ^C NHC (177.1–180.3 ppm) 12 and monoanionic N^N (164.5–172.6 ppm), 13 or N^C sp2 (183.6–184.7 ppm) 14 ligands (Fig.…”
mentioning
confidence: 99%
“…Complexes 3a–d and 4a–d all contain the i Pr 2 -bimy carbene ligand making them suitable probes to measure the electron-donating strengths of the transoid L and L 2 ligands using Huynh's electronic parameters (HEP & HEP2). 11 The detailed results and discussions are given in the ESI †. Here, a summary of the HEP2 scale was drawn to showcase that the current C NHC ^C sp3 chelators are stronger donors than the charge-neutral N^N (158.2–163.4 ppm), C NHC ^C NHC (177.1–180.3 ppm) 12 and monoanionic N^N (164.5–172.6 ppm), 13 or N^C sp2 (183.6–184.7 ppm) 14 ligands (Fig.…”
mentioning
confidence: 99%
“…1(iii)). 9 The 13 C NMR signal of the benzimidazolinylidene carbon donor in [( i Pr 2 -bimy)PdBr 2 (L)] corresponds to the Huynh electronic parameter (HEP) (where better donor ligands lead to lower field shifts), and Huynh has shown that the 13 C carbenic NHC signal in [( i Pr 2 -bimy)Au(L)] + complexes can be directly correlated to the HEP for carbene ligands (this has yet to be expanded to other ligand classes). Given that Fe(0) has previously been reported to form complexes with gold fragments, 4 a , b we envisioned that the synthesis of bimetallic compounds of the type [( i Pr 2 -bimy)Au–Fe(CO) 3 (PR 3 ) 2 ][BAr F 4 ] {BAr F 4 = tetrakis(pentafluorophenyl)borate} might allow an accurate ordering and comparison of the donor strengths of Fe(0) complexes as ligands.…”
mentioning
confidence: 99%
“…In addition, the selenium adduct of C (R = H) has been prepared and the π-acceptor strength of the CAAC has been determined by 77 Se NMR spectroscopy using the Ganters method . To complete the characterization of the benzannulated CAACs of type C , we now determined their σ-donor properties using the Huynh electronic parameter (HEP). , To this end, complex [ 5 ] was reacted with 1,3-diisopropyl-benzimidazolium tetrafluoroborate (bimy·HBF 4 ) in the presence of a base in acetone to give the CAAC–Au–NHC complex [ 6 ]­BF 4 (Scheme , see the SI). The HEP can then be calculated from the chemical shift δ­(C bimy ) in the 13 C NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%